1st, 2nd, and next generation LANs - Minoli, Daniel 1952- (McGraw-Hill series on computer communications, 1994)
Provides a comprehensive guide to networking options currently on the market and those soon to become available. The author describes the latest developments in ATM-based LANs, the latest LAN interconnection technologies such as frame relay and cell relay, FDDI, FDDI II and FCS.